Reinforcing Mechanism of WC Particles in Fe-Based Amorphous Matrix Coating on Magnesium Alloy Surface - Haoran Zhang (MDPI AG, 2021)
To protect magnesium alloy surfaces from wear and corrosion, an Fe-based amorphous coating was prepared on WE43 through the Ni60 interlayer by high-velocity oxygen-fuel (HVOF) spraying. The porosity was ~1%, and the amorphous content exceeded 90%. The wear and corrosion resistance of the composite coating with WC particles wrapped in a Ni layer as the reinforcing phase were compared with that of the completely amorphous coating. The friction coefficient (COF) of the composite coating was 0.3, which is only half of that of the WE43 substrate, and the composite coating exhibited a more stable wear behavior than the completely amorphous coating. The corrosion tendency of the composite coating is lower than that of stainless steel, with a corrosion potential of −0.331 V, and the addition of WC particles did not deteriorate the corrosion resistance considerably. The bonding mechanism of the bonding interface between the amorphous structure and the particles of the reinforcing phase was investigated by transmission electron microscopy (TEM). Reinforcing particles were confirmed to form metallurgical bonding with the coating. It was found that the Ni layer showed excellent bonding performance in the form of a mixture that is amorphous and nanocrystalline. Therefore, the Fe-based amorphous composite coating on a magnesium alloy surface shows a potential protective effect.